Eksistensi Pesantren Dalam Sistem Pendidikan Nasional - Muhammad Rusdi Rasyid (LPPM IAIN Sorong, 2015)
Islamic Boarding School as an institution of Islamic education in Indonesia has become a part of nation journey. In historical aspect, boarding school takes part from struggle history and boarding school has been taking part in nation culture. In education system, boarding school as an institution of Islamic education became sub-system from national education system. But, in a long history, boarding school has not shown their existence which can give shape to expectation for all people. This case may be caused by some factors, namely history, culture of national education system that causes Islamic boarding school left behind. As we know that in 1999 as a popular year to appear desentralisation and it becomes urgent moment to change culture system and education system, including Islamic boarding school.